ETIKA KOMUNIKASI ANAK PADA KELUARGA DALAM ISLAM - Noormawanti Noormawanti (Jurnal Bimbingan Penyuluhan Islam, 2021)
Family is a place where a child socializes. Socializing activities in the family carried out by a child are domestic socialization activities. It is in the family that a child recognizes and gets his identity. Therefore, in the process of family communication, the position of parents must be able to provide and foster a sense of kinship to all family members in the house, because the helmet can have a positive impact on all family members. The family will be a place for all to convey and a place to pour out their hearts, feelings and thoughts whenever children have problems and want something. The emergence of family relationships that are based on intensive communication relationships from all family members, especially children and parents, then the child will be more confident and motivated, especially on positive things to carry out orders and suggestions from parents so that children are always on His way.